Strengthening Academic Libraries: Quality Assurance Planning and Development Office’s Role in Digital Resilience and Risk Management - Montano, Mary Rose; Gonzales, Ronald A; Alba, Simplicio P; Opeña, Anna Rhea C; Garma, Marilyn R; Salenga Jr, Armando A; Malitig, Francis Eduard T; Rodelas, Lyka B; Navarro, Michael S (Center for Risk Management & Sustainability and RSF Press, 2026)
Libraries increasingly face complex risks threatening both physical and digital collections; however, empirical qualitative evidence on how institutional risk governance structures operationalize digital resilience remains limited. This qualitative case study examines the risk preparedness of 20 academic libraries within a bounded higher education governance context through open-ended questionnaires and policy document review. Findings indicate that while basic physical safeguards and manual digital backups are widely practiced, libraries lack formalized disaster recovery frameworks, cybersecurity protocols, and governance-aligned digital risk strategies. Crucially, the Quality Assurance, Planning, and Development Office (QAPDO) emerges not merely as a support unit but as a governance leverage point, capable of translating risk awareness into institutional obligation through policy alignment, strategic planning, accreditation-linked monitoring, capacity building, and resource mobilization. The study advances institutional resilience scholarship by reframing digital resilience from a technical or library-specific concern into an institutional governance capacity, demonstrating how QAPDO can re-couple fragmented library practices with central quality assurance systems. The study proposes a governance-centered conceptual framework that positions QAPDO as the mediating mechanism between institutional risk environments and sustainable digital resilience outcomes, offering a replicable model for embedding resilience into higher education library governance.